Structural change, aggregate demand and employment dynamics in the OECD, 1970 - 2010 - Jochen Hartwig (ETH Zurich, KOF Swiss Economic Institute, 2013)
The paper combines Baumol's model of structural change with a model of aggregate demand growth in the Keynesian-Kaleckian tradition to predict the dynamics of aggregate employment. The model for the demand regime is estimated with - and Baumol's model for the productivity regime is calibrated on - OECD data. The trajectory for employment predicted by the combination of the two models tracks the actual employment dynamics in the OECD over the period 1970-2010 remarkably well.
Keywords: C23; E12; E13; E20; O41; 330; Structural change; demand growth; productivity growth; employment dynamics; OECD panel data